TOPSIS-AHP HYBRID FOR COMPUTER LABORATORY HEAD SELECTION: INTEGRATION OF TECHNICAL, MANAGERIAL, AND PEDAGOGIC CRITERIA - Irawan, Feri; Putri, Perra Budiarti Rahayu; SLAM, Berta Erwin; Efranda, Nolan; Herikson, Rifaldi (Smart Education, 2025)
Abstract: The selection of the Head of the Computer Laboratory is a process that requires multidimensional considerations, including technical competence, managerial skills, pedagogic skills, communication, as well as work ethics and discipline. Subjectivity or seniority-based selection approaches often do not produce optimal laboratory leaders. This study aims to design and develop SPK based on the integration of AHP and TOPSIS methods as a means to conduct a methodical and unbiased selection of candidates. The stages carried out include: identification of five main criteria based on expert interviews, weighting of criteria using AHP, collection of candidate assessment data, and final ranking using TOPSIS. The weighting results showed that the Technical criteria had the highest weight of 0.416, followed by Managerial (0.211) and Pedagogic (0.171). Of the ten candidates analyzed, Candidate I obtained the highest preference score of 0.659, indicating a high balance of scores on all three main criteria. Logical validation tests and sensitivity analysis to weight changes showed that the system remained stable, with the position of Candidate I remaining in the first rank despite the change in the weight of the technical criteria (from 0.3 to 0.5). These findings prove that SPK based on AHP-TOPSIS is able to reduce subjectivity and provide consistent and reliable recommendations in the selection process for the Head of Computer Laboratory. Keyword: DSS, TOPSIS, Laboratory, Technical-Managerial-Pedagogic, AHP Abstrak: Pemilihan Kepala Laboratorium Komputer merupakan proses yang membutuhkan pertimbangan multidimensi, meliputi kompetensi teknis, kemampuan manajerial, keterampilan pedagogik, komunikasi, serta etika dan disiplin kerja. Pendekatan seleksi berbasis subjektivitas atau senioritas sering kali tidak menghasilkan pemimpin laboratorium yang optimal. Studi ini bertujuan merancang dan mengembangkan SPK berbasis integrasi metode AHP dan TOPSIS sebagai sarana untuk melakukan seleksi kandidat secara metodis dan tidak bias. Tahapan yang dilakukan meliputi: identifikasi lima kriteria utama berdasarkan wawancara pakar, pembobotan kriteria menggunakan AHP, pengumpulan data penilaian kandidat, dan perankingan akhir menggunakan TOPSIS. Hasil pembobotan menunjukkan bahwa kriteria Teknis memiliki bobot tertinggi sebesar 0,416, diikuti Manajerial (0,211) dan Pedagogik (0,171). Dari sepuluh kandidat yang dianalisis, Kandidat I memperoleh skor preferensi tertinggi sebesar 0,659, menunjukkan keseimbangan nilai tinggi pada ketiga kriteria utama. Uji validasi logis dan analisis sensitivitas terhadap perubahan bobot menunjukkan bahwa sistem tetap stabil, dengan posisi Kandidat I tetap pada peringkat pertama meskipun bobot teknis berubah sifnifikan (dari 0,3 hingga 0,5), hal ini menunjukan metode yang digunakan konsisten dan handal. Temuan ini menunjukan bahwa SPK berbasis AHP-TOPSIS mampu mengurangi subjektivitas dan memberikan rekomendasi yang konsisten serta dapat diandalkan dalam proses seleksi Kepala Laboratorium Komputer. Kata Kunci: SPK, TOPSIS, Laboratorium, Teknis-Manajerial-Pedagogik, AHP